Perlindungan Hukum yang Diberikan terhadap Anak yang Menjadi Korban Kekerasan Seksual di Lingkungan Pondok Pesantren - Muhammad Dacha Ramadhan; Hari Soeskandi (CV. Era Digital Nusantara, 2023)
Sexual violence is an act, whether in the form of speech or deed that is carried out by a person with the aim of controlling and getting other people involved in sexual activity which the person does not want. This study aims to analyze the legal protection given to children who are victims of sexual violence in Islamic boarding schools. The type of research used is normative by using the statutory approach, and the conceptual approach. The results of this study obtained that legal protection for children who are victims of sexual violence in Islamic boarding schools has been specifically regulated by Law No. 35 of 2014 concerning Amendment to Law Number 23 of 2002 concerning Child Protection, sexual violence in the Islamic boarding school environment is still classified as a child - child. This results in many impacts that will affect the psychological, physical, and social condition of a child when he becomes a victim of sexual violence. Child victims of sexual violence will experience tremendous trauma, children will tend to be more reserved, afraid, and anxious when they are with adults, easily angry and disappointed if the perpetrators can be accepted back into society even though the perpetrators have undergone punishment as a consequence of being implemented through reproductive health education efforts , religious and moral values, social rehabilitation, psychosocial support during treatment to recovery, providing protection and assistance at every level of investigation, prosecution, and trial in court.